Tandem metabolic reaction–based sensors unlock in vivo metabolomics - Xuanbing Cheng; Zongqi Li; Jialun Zhu; Jingyu Wang; Ruyi Huang; Lewis W. Yu; Shuyu Lin; Sarah Forman; Evelina Gromilina; Sameera Puri; Pritesh Patel; Mohammadreza Bahramian; et al. (Proceedings of the National Academy of Sciences, 2025)
Mimicking metabolic pathways on electrodes enables in vivo metabolite monitoring for decoding metabolism. Conventional in vivo sensors cannot accommodate underlying complex reactions involving multiple enzymes and cofactors, addressing only a fraction of enzymatic reactions for few metabolites. We devised a single-wall-carbon-nanotube-electrode architecture supporting tandem metabolic pathway–like reactions linkable to oxidoreductase-based electrochemical analysis, making a vast majority of metabolites detectable in vivo. This architecture robustly integrates cofactors, self-mediates reactions at maximum enzyme capacity, and facilitates metabolite intermediation/detection and interference inactivation through multifunctional enzymatic use. Accordingly, we developed sensors targeting 12 metabolites, with 100-fold-enhanced signal-to-noise ratio and days-long stability. Leveraging these sensors, we monitored trace endogenous metabolites in sweat/saliva for noninvasive health monitoring, and a bacterial metabolite in the brain, marking a key milestone for unraveling gut microbiota–brain axis dynamics.